Characterization and in vitro permeation study of microemulsions and liquid crystalline systems containing the anticholinesterase alkaloidal extract from Tabernaemontana divaricata - Wantida Chaiyana (2018)
The aims of the present study were to characterize the microstructure and study the skin permeation enhancement of formulations containing the alkaloidal extract from Tabernaemontana divaricata. The extract was loaded in the formulations composed of Zingiber cassumunar oil, Triton X-114, ethanol and water with the oil:surfactant ratios of 1:5 and 2:5. The formulations were characterized by photon correlation spectroscopy, polarizing light microscopy, differential scanning calorimetry, and viscosity measurement. A reverse micellar phase, w/o microemulsions, liquid crystalline systems, liquid crystal in microemulsion systems and coarse emulsions were formed along the aqueous dilution line of both oil:surfactant ratios. Formulations with the ratio of 1:5 containing 0.1 μg/ml extract showed a significantly higher acetylcholinesterase inhibition than those with the ratio of 2:5. The skin of stillborn piglet was used in the permeation study. The liquid crystalline and microemulsion systems significantly increased the transdermal delivery of the extract within 24 h. It was concluded that the alkaloidal extract from T. divaricata stem loaded in liquid crystalline or microemulsion systems comprising Z. cassumunar oil/Triton X-114/ethanol/water may act as an alternative percutanous formulations for enhancing the acetylcholine level in Alzheimer's patients. © 2013 Elsevier B.V. All rights reserved.